Elektrografie : Analoge und digitale Bilder - Urbons, Klaus; Alcala, José R.; Bleus, Guy; Brunet-Weinmann, Monique; Dar, Dina; Franke, Herbert W.; Friedman, Ken; Henss-Dewald, Roland; Huemer, Peter; Mühleck, Georg; Sachsse, Rolf; Sheridan, Sonia (Köln : DuMont Buchverlag, 1994)
Warhol, Andy ; VanDerBeek, Stan ; Sheridan, Sonia ; Alcalacanales ; Bleus, Guy ; Dar, Dina ; Helbig, H. ; Franke, H.W. ; Henss-Dewald, Roland ; Huemer, Peter ; Charbonneau, Jacques ; John, Franz ; Urbons, Klaus ; Mathiaut, Jean ; Kadar, Joseph ; trust, Com ; Beyelschmidt, Rosy ; Siepmann, Klaus ; Olbrich, Jürgen O. ; Hamilton, Richard ; Paik, Nam June ; Hainke, Wolfgang ; Durand, James ; Huemer, Peter ; Franke, Herbert W. ; Chevalier, Miguel ; Presser, Beat ; Denti, Giuseppe ; Alcala, José Ramon ; John, Franz ; Siekmann, Jochen C. ; Bär, Holger ; Mathiaut, Jean ; Dar, Dina ; Barron, Stephan ; Pawson, Mark ; Duarte, Sergio ; Megert, Franziska ; Pellini, Pietro ; Brynntrup, Michael ; Charbonneau, Jacques ; Sen, Quido ; Gonzalez, Marisa ; Czerny, Paul ; Belzner, Friedrich ; Mühleck, Georg ; Kerkhoff, Ina ; Cabanis, Daniel ; Wille, Helmke / Huch / Urbons / ; Berbesz, Yola ; Helmke, Peter ; Eckenbach, Manuela ; Van Geluwe, Johan ; Thurz, Udo ; Möller, Karl-Hermann ; Bär, Holger ; Badura, Michael ; Robic, Jean-François
Bibliografie
Duits
boek